2019
DOI: 10.1037/ort0000422
|View full text |Cite
|
Sign up to set email alerts
|

Ethnocultural diversity in alcohol use and misuse.

Abstract: Hazardous alcohol use is associated with deleterious health effects and social consequences, reduced work productivity, and increased medical and criminal justice expenditures. Research has consistently shown not only ethnic differences in prevalence rates of drinking behaviors and alcohol use disorders but also negative alcohol-related consequences and treatment-seeking patterns. Mainstream alcohol research has tended to focus on determinants and mechanisms that are common across ethnocultural groups; hence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Research has shown Hispanic-White differences in the onset and maintenance of alcohol-related problems in the general United States population (Caetano & Clark, 1998;Grant et al, 2012;Ríos-Bedoya & Freile-Salinas, 2014). 1 Hispanic individuals report disproportionately higher rates of binge drinking; even when controlling for levels of assumption, they experience more negative alcohol-related consequences than their White counterparts (Lui & Zamboanga, 2019;Mulia et al, 2017). Furthermore, Hispanic and other ethnic/racial minority individuals experience greater disease burden of alcohol use disorders than their White peers because of greater exposure to social disadvantages (Mulia, 2009;Mulia et al, 2008).…”
Section: Ethnic/racial Differences In Alcohol Use: Does Drinking Refu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown Hispanic-White differences in the onset and maintenance of alcohol-related problems in the general United States population (Caetano & Clark, 1998;Grant et al, 2012;Ríos-Bedoya & Freile-Salinas, 2014). 1 Hispanic individuals report disproportionately higher rates of binge drinking; even when controlling for levels of assumption, they experience more negative alcohol-related consequences than their White counterparts (Lui & Zamboanga, 2019;Mulia et al, 2017). Furthermore, Hispanic and other ethnic/racial minority individuals experience greater disease burden of alcohol use disorders than their White peers because of greater exposure to social disadvantages (Mulia, 2009;Mulia et al, 2008).…”
Section: Ethnic/racial Differences In Alcohol Use: Does Drinking Refu...mentioning
confidence: 99%
“…Relatively few studies have emphasized the possible roles of malleable psychological factors in explaining these group differences, and consider distinctive effects of these factors in understudied population (Lui & Zamboanga, 2019). To advance alcohol research and address ethnic/racial disparities in drinking, there is a critical need to move beyond the "black box" model of investigation (Malone et al, 2012).…”
Section: Hispanic Alcohol Use and Ethnic/racial Disparitiesmentioning
confidence: 99%
“…According to the latest global status report on alcohol and health by the World Health Organization (WHO), the South‐East Asian Region (SEAR) has the second lowest Alcohol‐Per capita‐Consumption (APC) in the world (World Health Organization, 2018). Cultural and social factors are known to affect the drinking behaviors of Asian subjects, who show the lowest alcohol consumption levels compared to other ethnicities (Lui & Zamboanga, 2019). APC levels have been increasing in the SEAR, but the percentage of current drinkers did not significantly change, being constant at around 33% from 2000 to 2016 (World Health Organization, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Given that depressive symptoms and alcohol use are strongly comorbid (Brière et al, 2014), AAM who report the former due to gendered racism may concurrently consume alcohol to cope and/or engage in other maladaptive risky behavior to regulate negative affect (Weiss et al, 2015). Alcohol-related problems are indeed an underrecognized (Cheng et al, 2018), ethnically heterogeneous (Kane et al, 2017;Lui & Zamboanga, 2018, 2019), yet increasing public health problem among Asian Americans (Iwamoto et al, 2012(Iwamoto et al, , 2016, with racial discrimination representing an epidemiological risk factor (Gee et al, 2007), and where AAM are vulnerable to substance abuse disorder (Cheng et al, 2012;Zamboanga et al, 2017).…”
mentioning
confidence: 99%